Development of ULTAGRAM Media Based on Quizwhizzer in an Effort to Increase Interest and Learning Outcomes - Tazkia Nurul 'Aini; Ika Ratnaningrum (Postgraduate, University of Mataram, 2025)
The role of learning media is crucial in enhancing the educational experience, helping students engage with the material and optimize their learning achievements. This study aimed to outline the design, assess the feasibility, and evaluate the effectiveness of ULTAGRAM learning media, which utilizes Quizwhizzer, specifically for the Pictogram topic in Mathematics for fourth-grade students at SDN Pakintelan 02. ULTAGRAM media is an acronym for media Ular Tangga Piktogram. The research was conducted as a development method using the ADDIE model, which encompasses five phases: problem analysis, product design, product development, product implementation, and product evaluation. Data were gathered through interviews, observations, surveys, and tests (pretest-posttest). The analysis of data involved normality tests to ensure that the data was normally distributed, homogeneity tests to ensure that the data was homogeneous, T-tests to determine the influence of the media, and N-Gain tests to determine the effectiveness of media use. The findings from this development research demonstrate that the ULTAGRAM media, based on Quizwhizzer, was successfully created and received a very favorable assessment from both material and media experts based on a validation test using a questionnaire, each of which received a score of 92 % with a very feasible category. Furthermore, the evaluation of the research data regarding the development of ULTAGRAM learning media indicates that it was effectively designed and significantly enhanced the interest and learning outcomes of fourth-grade students regarding Pictogram concepts at SDN Pakintelan 02 seen from the average increase in student learning outcomes from 65 to 80 and the percentage of learning interest questionnaires which increased by 43%.